Peningkatan Kompetensi Publikasi Ilmiah Melalui Workshop Penulisan Artikel Berbasis Struktur IMRAD dan Manajemen Referensi Digital - Oktovina Deci Rahakbauw; Albiansyah Albiansyah; Desika Andriani; Sri Rahayu; Ida Adhani (Jurnal Dehasen Mengabdi, 2026)
Scientific publication productivity is a crucial indicator in measuring lecturer performance and university reputation, especially in facing LAMEMBA accreditation. However, many lecturers face technical obstacles in converting research results into journal manuscripts ready for publication. This internal Community Service (PKM) activity aims to improve the competence of STIE Bhakti Pembangunan lecturers in compiling scientific articles based on the IMRAD structure and reference management. The implementation method uses an andragogical approach through interactive lectures, manuscript clinics, and hands-on practice attended by 28 permanent lecturers. Material management is centralized using cloud computing technology to prevent data loss. The results of the activity indicate an increase in participants' understanding and practical skills in mapping research gaps, compiling article frameworks, and using reference software automatically. This activity produced participant article drafts and e-certificates as fulfillment of administrative workloads (SIBKD). It is hoped that this program will continue with the formation of a Publication Clinic to assist the submission process to the acceptance stage in reputable journals.